Oiseaux de proie diurnes - Vincent L’Hérault; Kristen Peck; Laurent Nikolaiczuk; Erik Hedlin; Mikaël Jaffré; Barry G. Robinson; Joël Bêty; Philippe Galipeau; Alastair Franke; Alexandre Anctil; Vincent Lamarre (Le Naturaliste canadien, 2014)
The historical decline of the peregrine falcon (Falco peregrinus) in North America during the 20th century was mainly attributed to reproductive failure due to the accumulation of persistent organochloride pollutants. As a direct result to this finding, the Arctic Raptor Project was established in 1982, and its goal was to monitor the breeding success of Arctic-nesting peregrine falcons (F.p. tundrius). The present article provides a synopsis of the major findings of its research, which was principally conducted around Rankin Inlet (Nunavut), but also, more recently, around Igloolik and on Baffin Island (Nunavut). The results cover raptor feeding regimes, reproductive phenology, growth and survival of young, and population dynamics. The long-term Rankin Inlet study has identified, among other things, a decrease in the number of young fledged over the past 3 decades. Episodes of heavy summer rain, which have occurred more frequently in recent years, appear, in part, to be responsible for this decline in reproductive output. The continued study of Arctic-nesting raptors is crucial to our understanding of population dynamics, including how these are affected by changes in climate and in the environment (e.g., reductions in organochloride pollutant levels), and on the structure and functioning of the Arctic ecosystem. Le déclin historique du faucon pèlerin (Falco peregrinus) observé en Amérique du Nord au milieu du xxe siècle a été principalement attribué à l’échec de reproduction causé par les polluants organochlorés persistants. C’est dans ce contexte que le Arctic Raptor Project a été initié, en 1982, dans le but d’étudier la reproduction de faucons pèlerins F.p. tundrius nichant dans l’Arctique. Nous présentons ici une synthèse des principaux travaux conduits dans le cadre de ce programme de recherche réalisé essentiellement dans la région de Rankin Inlet, mais aussi plus récemment près d’Igloolik et sur l’île de Baffin au Nunavut. Des résultats portant sur le régime alimentaire, la phénologie de la ...